2017
DOI: 10.1002/eap.1438
|View full text |Cite
|
Sign up to set email alerts
|

Integrating field and satellite data for spatially explicit inference on the density of threatened arboreal primates

Abstract: Spatially explicit models of animal abundance are a critical tool to inform conservation planning and management. However, they require the availability of spatially diffuse environmental predictors of abundance, which may be challenging, especially in complex and heterogeneous habitats. This is particularly the case for tropical mammals, such as nonhuman primates, that depend on multi-layered and species-rich tree canopy coverage, which is usually measured through a limited sample of ground plots. We develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…() and September to November 2015 by Cavada et al. () (number of primate social groups detected in Supporting Information). Data collected followed the distance sampling approach (Buckland et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…() and September to November 2015 by Cavada et al. () (number of primate social groups detected in Supporting Information). Data collected followed the distance sampling approach (Buckland et al.…”
Section: Methodsmentioning
confidence: 99%
“…Primate data were collected July 2011 to February 2012 and August to November 2012 by Araldi et al (2014) and Barelli et al (2015) and September to November 2015 by Cavada et al (2017b) (number of primate social groups detected in Supporting Information). Data collected followed the distance sampling approach (Buckland et al 2001); 2-km-long transects were uniformly distributed in each forest block according to a randomly placed grid ( Fig.…”
Section: Primate and Habitat Datamentioning
confidence: 99%
“…One study found that the null model was the best-fitting model in two of four cases (Major, Buxton, Schacter, Conners, & Jones, 2017), suggesting little support for the ecological hypotheses of interest. Several papers examined the match between observed and fitted values for an averaged model (Edwards, Massam, Haugaasen, & Gilroy, 2017;Mitchell, Bakker, Vincent, & Davies, 2017), while another undertook cross-validation on a model-averaged result (Cavada et al, 2017). The other 64 papers did not evaluate model goodness-of-fit in an absolute sense.…”
Section: The Best Models Frequently Are Not Assessedmentioning
confidence: 99%
“…Species abundance can be measured in several ways useful for classifying vegetation communities (Kent 2012) and in Queensland the recommended data collection methodology focuses on three; basal area, stem counts and percentage cover . All of these can be used to estimate relative dominance and abundance (for example (Lehmann et al 2014;Memiaghe et al 2016;Cavada et al 2017;Eldridge et al 2018); however, the arguments supporting the use of percentage cover as the abundance measure in quantitative class definition procedures for the RE system are compelling. The most common abundance measure used globally in vegetation classification systems (De Cáceres et al 2018) is percentage cover and within Australia it is used to determine national vegetation types (Executive Steering Committee for Australian Vegetation Information and Department of the Environment and Heritage 2003; Hnatiuk et al 2009).…”
Section: Species Abundance Measurementioning
confidence: 99%